Yeni uygur Türkçesinde tümce biçimdeki deyimler - İdikut, Mihrigül (My University, 2024)
Deyim, bir ulusun kültürel özelliklerini yansıtan önemli bir dil birimi olarak hep dikkat çekmektedir. Deyimler, anlatıma akıcılık ve çekicilik katan, genellikle gerçek anlamının dışında kullanılan, toplumun benimsediği kalıplaşmış söz öbekleridir. Bu nedenle deyimler parçalanamaz ya da sözcükleri eş anlamlı bile olsa başka bir sözcükle değiştirilemez, değiştirildiği takdirde de ifade etmek istediği anlamı vermezler. Deyimler birden çok yapısal özellik gösterirler. Bazı deyimler, tümce yapılarında kalıplaşmışlardır. Bu çalışmada Yeni Uygur Türkçesindeki tümce biçimlerindeki deyimler derlenerek incelenmiştir. Derleme aşamasında Harut Resul Kadiri tarafından Sincan Halk Neşriyatı yayımladığı Uygur İdiyomlar Logäti kitabı, Milletler Neşriyatında yayınlanan Uygur Tilinin İzahli Lügati, Kazakistan'da Camalidinof Öktäbir tarafından yayınlanan Uygur Tilinin Frazeologiyä Logäti ve Abdusalam Abbas tarafından Sincan Halk Neşriyatında yayınlanan Uygur Frazeologiysinin İzahli Logäti kaynak olarak kullanılmıştır. İnceleme kısmında metindeki tümce biçimindeki deyimler tümce türleri bakımından incelenmiştir. Metinde, derlenen deyimler Yeni Uygur Arap alfabesiyle yazılıp Yeni Uygur Türkçesi konuşma diline uygun olarak transkripsiyonu yapılmıştır. Deyimlerin anlamları da açıklanarak yazılmıştır. Son olarak dizin kısmında deyimleri oluşturan kurucu sözcükler ve birleşik sözcüklerin dizini yapılmıştır.

Idioms always attract attention as an important linguistic unit that reflects the cultural characteristics of a nation. Idioms are stereotyped phrases adopted by society that add fluency and attractiveness to the expression and are often used outside of their real meaning. Therefore statements cannot be separated or words cannot be replaced with another word even if they are synonymous, If they are changed, they will not give the meaning they want to express. Idioms show more than one structural feature. Some idioms are stereotyped in their sentence structures. In this study, idioms in sentence forms in New Uyghur Turkish were compiled and examined. The studies used as sources during the compilation phase are Uyghur Idioms Dictionary published by Harut Resul Kadiri in Xinjiang Halk Publications, The Explanatory Dictionary of the Uyghur Language in Contemporary published by Milletler Publication, The Uygur Tilinin Frazeologiyä Logäti- Phraseological Dictionary of the Uyghur Language published by Camalidinof Öktäbir in Kazakhstan and Explanatory Dictionary of Uyghur Phraseology published by Abdusalam Abbas in Xinjiang Folk Publications. In the analysis part, the sentence-form idioms in the text were examined in terms of sentence types. In the text, the compiled idioms were written in the New Uyghur Arabic alphabet and transcribed following the New Uyghur Turkish spoken language. The meanings of the idioms are also written by explaining. Finally, the constituent words and compound words that make up the idioms are indexed in the index section.
Keywords: Deyimler; Dilbilgisi; Grammar; Idioms; Idioms in Sentence Form; New Uyghur Turkish Language; New Uyghur Turkish Language Idioms; Sentence; Tümce; Tümce Biçimindeki Deyimler; Uighur language; Uygur dili; Yeni Uygur Türkçesi; Yeni Uygur Türkçesi Deyimler